Immigrant Entrepreneurship in an Emerging Economy: The Case of Turkey - ZAMANTILI NAYIR, DİLEK (WILEY, 2019)
This paper examines motivations for, and paths to, entrepreneurship among immigrants in Turkey based on interviews with 22 immigrant entrepreneurs in Istanbul. Findings suggest that immigrant entrepreneurs in a developing economy may be different from their counterparts in well-established economies. First, immigrant entrepreneurs rely on their unique human and social capital in the process of starting businesses thanks to their ability to identify opportunities based on insider knowledge of the market in their home and host countries. Second, their ability to foster trusting relationships thanks to language, cultural, and religious knowledge permits immigrant entrepreneurs in an emerging economy to engage in less economically marginal activities.
Keywords: ETHNIC ENTERPRISE; SELF-EMPLOYMENT; MOTIVATIONS; CHINESE